Kualitas Udara Dalam Ruang Rawat Inap Di Rumah Sakit Swasta Tipe C Kota Pekanbaru Ditinjau Dari Kualitas Fisik - Endang Purnawati Rahayu; Zulfan Saam; Sukendi Sukendi; Dedi Afandi (Dinamika Lingkungan Indonesia, 2019)
Good indoor air quality is free from pollution which can cause irritation, discomfort and occupant health. One room that can be polluted is an inpatient room. to determine the value of air quality in an inpatient room in terms of physical quality. The method used is observation and measurement regarding temperature, humidity and dust of the hospital. The results showed the average temperature of the week in the inpatient room for VIP, class 1, 2, and 3 classes has exceeded the standard quality value. The average humidity of the week in the VIP class and class 1 does not exceed the value of quality standards, in grades 2 and 3 have exceeded the standard quality value. While the average dust per week only in the VIP class, 1 and 2 does not exceed the quality standard, but in class 3 has exceeded the standard quality value. The advice given to hospitals is to do Air Conditioner maintenance on a regular basis, monitoring temperature, humidity and dust in every room as well as routine room cleaning.